(untitled) (Journal of Hama University, 2021)
Restoration of highly dilapidated anterior primary teeth is considered to be one of the major challenges that face any pediatric dentist. As a conventional procedure, appropriate endodontic treatment must be performed to these teeth before any restorative or compensative procedure. Evaluating the effect of different materials used in filling the root canals on the bonding strength of three types of posts in the primary anterior teeth. The sample consisted of 90 extracted primary canines. A complete pulpectomy was performed for all of the sample teeth. The sample were divided into two main groups, each of them contains 45 teeth according to the filling material type, group1: Metapex, group2: Zinc oxide and Eugenol paste, three types of posts were used to construct the teeth . the push-out test was performed by the Mechanical Test Machine. The results were statistically analyzed with Independent samples T-test. The values of the bonding strength were greater when using METAPEX than when using Zinc oxide and Eugenol paste in all groups of posts, but with significant differences only in the short composite posts group. The use of zinc oxide and eugenol paste as a root canal filling material resulted in a clear decrease in the bonding strength values of the various intra radical posts in the primary anterior teeth.